A Cross-sectional Study of Mental Health Effects of Excessive Screen Time and Social Media Use among Indian Adolescents and Young Adults - Sheikh Mohd Saleem; Shah Sumaya Jan (Wolters Kluwer Medknow Publications, 2024)
Introduction: The impact of excessive screen time and social media use on mental health, particularly among adolescents and young adults, has raised concerns. Objective: The objective of this study is to assess the mental health effects of excessive screen time and social media use among adolescents (13-19 years) and young adults (20-25 years) in India. Methods: This cross-sectional online survey study recruited 1392 participants (672 adolescents and 720 young adults) from India. Validated scales assessed mental health outcomes, screen time, social media use, mediating factors, and coping strategies. Descriptive statistics, correlation analyses, regression models, and thematic analysis were employed. Results: The prevalence of depression symptom was 37.9%, anxiety symptom was 33.3%, high stress 43.7%, and low self-esteem 25.3%, respectively. Significant positive correlations were found between screen time, social media use, and symptoms of depression (r = 0.32, r = 0.25), anxiety (r = 0.28, r = 0.22), and stress (r = 0.36, r = 0.29), while negative correlations existed with self-esteem (r = −0.25, r = −0.18). Poor sleep quality and cyberbullying exacerbated mental health issues, while physical activity and social support had protective effects. Common coping strategies included physical activity, hobbies, social support, digital detox, and mindfulness. Conclusions: The study provides compelling evidence linking excessive screen time and social media use with adverse mental health outcomes such as depression symptoms, anxiety symptoms, stress, and low self-esteem among Indian adolescents and young adults. Key mediating factors were poor sleep quality exacerbating mental health issues, while physical activity, social support, and reduced cyberbullying were protective. While recognizing technology's benefits, the study highlights promoting balanced digital habits, addressing underlying factors, and equipping youth with coping skills to foster a healthier relationship with technology and safeguard mental well-being.